Ulpian’s offer: The subjective value of the patrimonial nature of the contract - Escobar Rozas, Freddy (2014)
With respect to the patrimonial nature of thecontract, derived from the patrimonial nature of  the benefit, a lot has been written and proposed. Authors from different periods andwith different ideas have addressed the subject, since  it  is  fundamental  to  understand  thebasic concepts of obligation and contractualrelationship. The stance of the majority findsthe foundation of the patrimonial nature of the benefit in being a limit to private autonomy,since such  nature,  which  is  susceptible  ofeconomic value, is defined by the social context,and not by the parties.In this article, the author rejects and discusses the mentioned stance. Based on the liberty that each person has to determine what is more convenient for himself and what is more efficient in economic terms, the author defends a subjective vision of the patrimonial nature of the contractual relation, and gives a different function and foundation to the patrimonial nature of the benefit: Being essential for the calculation  of  the  compensation  in  case of breach.